In-situ and ex-situ upgrading of pyrolysis vapors from beetle-killed trees. (15th February 2016) - Luo, Guanqun; Resende, Fernando L.P.
Highlights: In-situ upgrading was significantly affected by the catalyst-to-biomass ratio. Ex-situ upgrading was significantly affected by the secondary reactor temperature. In-situ and ex-situ upgrading led to similar yield of aromatic hydrocarbons and HHV. In-situ upgrading led to more alkylated aromatics than ex-situ upgrading. Alkylation/dealkylation reactions controlled the product selectivity. Abstract: In this article, we systematically studied the effects of several parameters on the product yield and selectivity for the in-situ and ex-situ upgrading of pyrolysis vapors from beetle-killed trees using a micro-pyrolyzer equipped with an online GC/MS/FID. HZSM-5 was used as catalyst for both processes. The in-situ upgrading was highly affected by the catalyst-to-biomass ratio. At the ratio of 10, the highest aromatic yield of 25% was obtained with the carbonaceous residues yield of 41%. For the ex-situ upgrading, the most important variable to affect the product yield is the secondary reactor temperature. The highest aromatic yield of 22% and lowest coke yield of 14% was achieved at the secondary reactor temperature of 600 °C. Alkylation and dealkylation of alkyl aromatics over HZSM-5 played an important role in determining product selectivity in both processes. Dealkylation reactions were favored at higher temperature and the alkylation reactions were promoted at lower temperature, which is consistent with the exothermic nature of alkylation. A direct comparison between the in-situ and ex-situ upgrading processes was made under identical conditions. The comparison shows largely similar yields of aromatic volatiles and solid residues between the two upgrading processes, with differences primarily on species selectivity. As a result of the alkylation/dealkylation reactions, the in-situ upgrading had higher selectivity to xylenes and aromatics with nine carbons, and the ex-situ upgrading exhibited higher selectivity to benzene and toluene.